Assessment of schistosomiasis and soil‐transmitted helminths prevalence in school‐aged children and opportunities for integration of control in local health services in Kwilu Province, the Democratic Republic of the Congo. Issue 11 (14th September 2017) - Inocencio da Luz, R.; Linsuke, S.; Lutumba, P.; Hasker, E.; Boelaert, M.
Abstract: Objective: To determine the prevalence of schistosomiasis (SCH) and soil‐transmitted helminths (STH) in the Democratic Republic of Congo, and to assess the capacity of the local health centres for diagnosis and treatment. Methods: Cross‐sectional school‐based survey in two health districts in the Province of Kwilu. We collected a stool and a urine sample for parasitological examination. Urine filtration and duplicate Kato‐Katz thick smears were used for the diagnosis of SCH. Health centres were evaluated using a structured questionnaire. Results: In total, 526 children participated in the study and the overall prevalence of Schistosoma mansoni infection was 8.9% (95% CI: 3.5–13.2) in both districts. The prevalence was higher in Mosango (11.7%; 95% CI: 8.9–14.8) than Yasa Bonga district (6.2%; 95% CI: 1.1–11.4). Urine filtration showed that Schistosoma haematobium infection was not present. The combined STH infection prevalence was 58.1% in both districts; hookworm infection was the most common STH found in 52.9% (95% CI: 29.3–62.4) of subjects, followed by Ascaris lumbricoides 9.3% (95% CI: 5.8–15.5) and Trichuris trichiura 2.1% (95% CI: 0.9–4.9). Mixed STH infections were observed as well as SCH‐STH coinfection. Conclusion: Further mapping of both SCH and STH burden is needed, and coverage of preventive chemotherapy in school‐aged children should be increased.